EVALUATION OF EFFICIENCY OF DIGITIZATION OF HOUSING CONSTRUCTIONS IN KASHKADARYA REGION AND IMPROVEMENT OF MANAGEMENT MECHANISMS - Dexkanova Nilufar Sagdullayevna; Muratova Mahtuma Gapurovna; Sheripbayeva Umida; Normurodov Sarvar Norboy ugli (Scholar Express Journals, 2023)
In this article, the digitization of housing constructions in the Kashkadarya region, efficiency evaluation and improvement of management mechanisms, and the indicators of effectiveness achieved by using gadgets in lighting are mentioned
Keywords: Housing construction; motivation; performance; management mechanisms